A ROLE OF CORTICOSTEROIDS IS IN TREATMENT OF THE FIRST DIAGNOSED DESTRUCTIVE LUNG TUBERCULOSIS WITH PRIMARY DRUG-RESISTENT OF MYCOBAKTERIUM TUBERCULOSIS - Yareshko А.G.; Kulish, M.V.; Pos, O.A. (World of Medicine and Biology, 2012)
In 146 patients with the first diagnosed destructive lung tuberculosis with primary drug-resistent of mycobacterium tuberculosis (MBT) to antituberculosis preparations (ATP), with the purpose of determination of efficiency of CST, the clinic-statistical analysis of influence of CST is conducted on the indexes of hemogram, resolve of infiltration, halted secreting MBT and closing of cavities. It was set that CST is the important nosotropic mean of improvement of bearableness of chemotherapy, which allows to attain resolve of infiltration in 85,23% of patients of basic group, while in a control group – in 65,52% (р